Juan Francisco Sans: The precocious sage, the eternal child (Mayéutica Revista Científica de Humanidades y Artes, 2023)
This paper is a brief portrait of the musician, pianist, composer and musicologist Juan Francisco Sans, as perceived by someone who had the privilege of sharing friendship and professional projects with him.
Keywords: Keith Emerson; Pablo Hilario Giménez; José Rafael Lovera; José Antonio Calcaño; Mariantonia Palacios